2016
DOI: 10.3390/ijerph13121226
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Urbanization Modes on the Spatial Circulation of Flaviviruses within Ouagadougou (Burkina Faso)

Abstract: Dengue is an emerging infectious disease of global significance. Although this virus has been reported for a long time, its significance within the burden of diseases in West Africa is not obvious, especially in Burkina Faso. Our objective was to evaluate flavivirus presence in Ouagadougou (Burkina Faso) and the link between anti-flavivirus antibody seroprevalence and urbanization modes. A population-based cross-sectional survey was conducted and 3015 children were enrolled from Ouagadougou districts with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 29 publications
(28 reference statements)
0
30
0
Order By: Relevance
“…Donors living in rural areas were 50% less likely to have a positive IgG anti‐DENV test than those living in Ouagadougou (OR = 0.47; IC = 0.33–0.65, P = 0.000). Vairo et al . in Zanzibar, reported that donors living in urban areas were three time more likely to be infected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Donors living in rural areas were 50% less likely to have a positive IgG anti‐DENV test than those living in Ouagadougou (OR = 0.47; IC = 0.33–0.65, P = 0.000). Vairo et al . in Zanzibar, reported that donors living in urban areas were three time more likely to be infected.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not perform an antibody neutralising assay to rule out cross‐reactions with other circulating flaviviruses. Indeed, as previous studies indicate regarding the circulation of other flaviviruses, the plaque reduction neutralisation test (PRNT) could have allowed us to determine antibody and serotype specificity. Moreover, it would have been necessary to perform a nucleic acid test (NAT) or at least serological tests for NS1Ag and IgM anti‐DENV to attempt to identify recent (primary or secondary) infections that are the most important concern for blood safety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations